Physiological and Chemical Responses of Tissue-Cultured Barhi and Hilali Date of Foliar Amino Acid Application - hanoon, Batool; Dinar, Ahmed (University of Thi-Qar Journal of agricultural research, 2025)
This study was conducted in one of the private orchards in Nasiriyah district, Thi- Qar Governorate, Iraq, during the growing season of 2023, with the aim of knowing the effect of spraying tissue-propagated Barhi and Hilali date palm trees cultivars with a mixture of some amino acids to improve fruit set, reduce the percentage of parthinocarpic fruits, and some chemical characteristics of fruits in the Hababok stage. The mixture of protein amino acids consisted of (L- Mithionine, L- Lysine, L- Glutamic, L- Arginine, and L- Tryptophan) at two concentrations (25 and 50) mg L-1 for each of them, in addition to their interactions and the comparison treatment. The results of the study showed that spraying with the mixture of amino acids led to a significant increase in each of the percentage of fruit set and concentrations of amino acids, total soluble proteins, and total soluble carbohydrates, and the concentration treatment (50 ml L-1) was significantly superior and achieved the highest averages of (72.83%), (6.95, 7.84, and 15.71) mg g-1, respectively. The concentration treatment (50 ml L-1) also achieved the lowest average of parthinocarpic fruits, reaching (24.41%). Regarding the cultivar effect, the Barhi cultivar significantly outperformed and achieved the highest averages for each of the percentage of fruit set and the fruit content of amino acids, total soluble proteins, and total soluble carbohydrates, reaching (68.98%), (5.42, 6.45, and 14.00) mg g-1, respectively, the Barhi cultivar also achieved the lowest average, with a significant difference, for the percentage of parthinocarpic fruit, reaching (30.58%), compared to the Hilali cultivar. Interaction coefficients between the study factors were significantly superior to the interaction treatment between the Barhi cultivar and amino acids at a concentration of (50 ml L-1), achieving the highest averages for each of the percentage of fruit set and its amino acid content, total soluble proteins and total soluble carbohydrates amounted to (74.68%) and (7.76, 8.63 and 18.47) mg g-1, respectively. This interaction treatment also achieved the lowest average and significant difference in the percentage of parthinocarpic fruits, reaching (21.83%) compared to the rest of the interaction treatments.